1034. RHODODENDRON POILANEI: Ericaceae. (26th August 2022) - Rushforth, Keith; Yamanaka, Masumi
Summary: Rhododendron poilanei Dop, from Vietnam and southwestern China is illustrated and its relationship with other species in section Peudovireya is discussed.